Preparation of liposomes containing whey proteins [Süt serumu protei̇nleri̇ni̇n li̇pozomlanmasi] - (:unkn) unknown (My University, 2010)
Aim: In recent years, it has been shown that whey and its components have a number of health-promoting effects. We aimed to isolate fractions containing whey proteins using chromatography and then to prepare antioxidant liposomes in order to obtain a gel suitable for cosmetic preparations. Methods: Fractionation of whey proteins was achieved by extraction, filtration and centrifugation followed by liquid chromatography. The antioxidant activities of the fractions was determined by their copper ion reducing capacity. Gel electrophoresis was used to analyze the proteins. Liposomes were made by the thin film hydration method. Results and Conclusion: Using Sephadex G-50 chromatography, two fractions were obtained. The first fraction contained major whey proteins, while the second fraction had small peptides. We have then determined the antioxidant activities of these fractions. The first fraction had the highest antioxidant activity. We prepared liposomes containing whey protein fractions and analyzed their sizes. Then, we investigated the liposome structures under a light microscope, electron microscope and atomic force microscope. Finally, we prepared a cosmetic formula from liposomes containing the whey fractions. We believe that preparing antioxidant liposomes containing whey proteins will be an important contribution to the cosmetic formulas for dermal applications.
Keywords: Antioxidant activity; Gel chromatography; Liposome; Whey proteins